Genetic Polymorphism of Interferon-Gamma +874T/A as a Risk Factor for Pulmonary Tuberculosis in Cirebon, Indonesia - Kiteswara, Allain Umadela Deuxawalu; Sari, Ariestya Indah Permata; Pratamawati, Tiar Masykuroh (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: Tuberculosis (TB) is one of the leading causes of death globally, caused by Mycobacterium tuberculosis. With 10% of all cases worldwide in 2022, Indonesia is the second-largest contributor of tuberculosis cases. IFN-γ gene polymorphism is one of the factors that have been studied extensively for its association with TB. Aims: To analyze IFN-γ +874T/A gene polymorphism as a risk factor for pulmonary tuberculosis in Cirebon. Methods: Observational analysis with case control design was used in this study. Thirty-two tuberculosis patients as cases and 32 healthy controls at RSUD Waled were collected and performed DNA extraction to evaluate the polymorphism by using Amplification-refractory mutation system–polymerase chain reaction (ARMS–PCR). Statistical comparison was performed by using Pearson Chi-square and Kruskal Wallis test. Mann-Whitney U test was done for post hoc test. Odds ratio was calculated to see the risk of the assessed variables, including genotype, allele frequency, and the presence of polymorphism. Results: In the case group, the frequency of TT genotype was 3 (9.4%), TA genotype was 26 (81.3%), AA genotype was 3 (9.4%). In the control group, the frequency of TT genotype was 12 (37.5%), TA genotype was 17 (53.1%), AA genotype was 3 (9.4%). A significant difference (p=0.034) was found among 3 genotype groups. Post hoc test revealed that TT and TA was the pair with significant difference (p=0.007). In addition, TA polymorphism was significantly associated (p=0.004) with tuberculosis (OR=6.614; CI95% = 1.660-26.349). Conclusion: IFN-γ +874 TA gene polymorphism is associated with pulmonary tuberculosis in the population of Cirebon, West Java, Indonesia. Received: 25 September 2024 | Reviewed: 23 October 2024 | Revised: 10 November 2024 | Accepted: 30 November 2024